Practical Prototype and script.aculo.us - Dupont, Andrew (Apress, 2012)
This book is also meant to appeal to those who have some experience with Prototype but don’t consider themselves experts. Many have worked with Prototype indirectly through Ruby on Rails or a similar framework. Many have used a third-party script that depended on Prototype, but treated the code as a black box. In the first chapter of the book, we’ll look at some aspects of the JavaScript language that novice users may not know about. Feel free to spend as much time on Chapter 1 as you need, since it’s crucial that you understand these concepts if you want to use Prototype effectively.p